1997
DOI: 10.1021/ma9616423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oligo(ethyleneoxy)cyclotriphosphazenes, Tetraglyme, and Other Small Molecules on the Ionic Conductivity of the Poly[bis(methoxyethoxyethoxy)phosphazene] (MEEP)/Lithium Triflate System

Abstract: Four small molecule cyclotriphosphazenes bearing linear and branched ethyleneoxy units have been synthesized as ion transport assistance (ITA) species to improve the ionic conductivity of poly-[bis(methoxyethoxyethoxy)phosphazene] (MEEP)-lithium triflate systems. The cyclotriphosphazenes were characterized by 31 P, 1 H, and 13 C nuclear magnetic resonance spectroscopy and infrared spectroscopy. MEEP was complexed with lithium triflate and combined with different amounts of each of the ITA molecules. Room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 25 publications
1
52
1
Order By: Relevance
“…1. The compounds, tri(methoxyethoxyethoxyethoxy)triazine (C 3 N 3 (OR) 3 ) and hexa(methoxyethoxyethoxyethoxy)cyclotriphosphazene (P 3 N 3 (OR) 6 ), were synthesized according to the method described in the literature [14]. Chlorotriazine (C 3 N 3 Cl 3 ) and hexachlorocyclotriphosphazene (P 3 N 3 Cl 6 ) were purchased from Alfa Aesar.…”
Section: Chemicals and Synthesis Of The Ilsmentioning
confidence: 99%
“…1. The compounds, tri(methoxyethoxyethoxyethoxy)triazine (C 3 N 3 (OR) 3 ) and hexa(methoxyethoxyethoxyethoxy)cyclotriphosphazene (P 3 N 3 (OR) 6 ), were synthesized according to the method described in the literature [14]. Chlorotriazine (C 3 N 3 Cl 3 ) and hexachlorocyclotriphosphazene (P 3 N 3 Cl 6 ) were purchased from Alfa Aesar.…”
Section: Chemicals and Synthesis Of The Ilsmentioning
confidence: 99%
“…It was also reported that these polymers have a high onset temperature of thermal degradation (235 • C) together with a modest heat release capacity [23]. Moreover, small molecule cyclic phosphazenes with the same ethyleneoxy side groups have been used either as stand-alone electrolytes or as plasticizers for gel electrolytes, and they are known to function well as solvents and as additives that increase the ionic conductivity of the base macromolecular electrolyte [24,25] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, ion-conducting polymers have been investigated as promising and safe alternatives to the commercially available electrolytes currently used in lithium batteries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The initial discoveries that polymer complexes could be used as either liquid [1] or solid [2] ionic conductors has led to the development of a wide range of polymer-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, PEO is crystalline at room temperature and can be electrochemically unstable. Therefore, efforts have focused on the combination of PEO with amorphous polymers such as polyphosphazenes [3][4][5][6][7][8] and polysiloxanes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] via copolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation